Pengembangan Inovasi Belajar dan Mengajar di Era Disrupsi Melalui Pembelajaran Daring dan Luring (Hybrid Learning System) - Robiatul Adawiya; Dyahsih Alin Sholihah; Rino Richardo; Ahmad Anis Abdullah; Muhamad Najib Mubarrak; Frida Nurul Azizah; , Frida Nurul Azizah; Lisa Ananda; Duwik Nur Cahyo (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Social activities can be a medium to share with others in need. Sharing for others can be done in the form of assisting in the world of education. In addition, social activities are also a form of implementation of the Tri Dharma of Higher Education, namely serving. This kind of activity can be an opportunity for students to share what they get with the community and increase their empathy for others. The research activity with the theme “Development of Teaching and Learning Innovation in the Era of Disruption through Online and Offline Learning (Hybrid Learning System)” is a community service activity carried out to increase innovation in learning during the pandemic through the Hybrid Learning System method where students majoring in mathematics education as teaching volunteers.